Evaluation of summer precipitation over Far East Asia and South Korea simulated by multiple regional climate models. (18th October 2019) - Park, Changyong; Cha, Dong‐Hyun; Kim, Gayoung; Lee, Gil; Lee, Dong‐Kyou; Suh, Myoung‐Seok; Hong, Song‐You; Ahn, Joong‐Bae; Min, Seung‐Ki
Abstract: The evaluation of climate model performance is necessary to enhance the reliability of available models. Recently, the interest in the added value has been increasing due to the continued enhancement of the horizontal model resolution for dynamical downscaling. We have examined the simulation performance of regional climate models (RCMs) forced by two global climate models (GCMs) for summer precipitation over Far East Asia and South Korea on the basis of spatial resolution improvement. In terms of model resolution, coarse‐resolution RCMs present limitations, whilst high‐resolution RCMs offer the added value as revealed by several performance evaluations. RCMs forced by HadGEM2‐AO estimated smaller summer precipitation over South Korea than those observed, whereas RCMs forced by MPI‐ESM‐LR presented a wet bias. Here, moderate‐heavy rain in RCMs forced by HadGEM2‐AO and light‐moderate rain in RCMs forced by MPI‐ESM‐LR were found to lead to dry and wet biases, respectively. Abstract : Spatial distributions of summer precipitation climatology: ( a, b) APHRODITE, ( c–f) biases of GCMs, and ( g–i) biases of MMEs of RCMs, and inter‐model agreements for simulated data sets over Far East Asia. The area‐averaged biases of Far East Asia and South Korea are expressed at the bottom of each panel. Stippling represents areas where all RCMs have the same bias sign.